Un garrot dans l’instrumentarium du médecin antique ? - Mélanie Lioux (Histoire, Médecine et Santé, 2016)
The presence of a small buckle placed inside a metal box containing eye drops among the furniture of the eye specialist kit of La Favorite (Gallo-Roman Museum of Lyon) has led us to consider this insignificant object as a medical instrument in itself. This discovery is not isolated but these elements have often been interpreted as leather cases residues. The assumption that they would be tourniquets has sometimes been suggested, but rarely relayed. The existence of tourniquets is however well attested in the Greco-Roman medicine. The examination of ancient medical treatises shows that it is not necessary to understand the bloodstream to witness empirically the effects of the indirect compression method. The study of textual sources and the archaeological context of the Lyon furniture invite us to reconsider this working hypothesis.